(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This paper aims to study the role of distributing surplus funds in enhancing trust in Islamic insurance products. The surplus refers to the financial amounts collected by Islamic insurance companies through premiums paid by participants, which exceed the actual costs of claims and expenses. This surplus is a vital element in Islamic insurance as it contributes to improving the company’s performance and enhances its transparency and reliability among participants. The study discusses how this surplus is managed and distributed to participants in compliance with Islamic principles, as well as its impact on strengthening trust and public acceptance of Islamic insurance products.